Levodopa-responsive progressive encephalomyelitis with rigidity and myoclonus associated with glycine receptor antibodies. (January 2021) - Sturchio, Andrea; Gastaldi, Matteo; Cariddi, Lucia Princiotta; Biacchi, Daniela; Espay, Alberto J.; Franciotta, Diego; Versino, Maurizio; Mauri, Marco
Highlights: New dopa-responsive phenotype expands the spectrum of GlyR antibody-associated PERM syndrome. Appendicular rigidity with axial hypotonia and oculomotor abnormalities suggested hypodopaminergic tone. Downstream effects GlyR antibody may interfere with the dopamine network.